The effect of high-intensity exercise on changes of blood concentration components in Algerian national judo athletes - Adel, B.; Abdelkader, B.; Alia, C.; Othman, B.; Mohamed, S.; Houcin, A. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2019)
The aim of the present study to verify the impact of judo competition on changes in the blood count of judo athletes during an official competition. Also to compare these results with the different weight category. Methods: fifteen youth trained athletes were included in the study were divided into three groups according to weight category (light, medial, and heavy) weight. All subjects performed a 5×4mn round of competition with 15mn of rest between rounds and Complete Blood Count (CBC) were collected before, immediately after the competition, Data are reported as mean and standard deviation. The Shapiro-Wilk test was performed to verify the normality of the data, and the significance level was set at P < 0.05. Blood sample count was tested by a paired Student`s t-test to compare the pre-test and post-test for the three groups. The results showed that blood cell count was significantly decreased immediately after judo competition (p < 0.05). However, red blood cell, White blood cell Blood platelets, Mean Cell Volume were significantly increased after the performance (p < 0.05). The current study showed that the judo competition (Rondori) effectively enhance some blood cell count; these changes are transient and probably due to the adaptation to efforts related to judo competition in highly-trained athletes.